Humic substance extraction from leonardite, lignite Mae Mho Mine by base-acid treatment process - Buntita Jomhataikool; Sanchai Kuboon; Wasawat Kraithong; Apiluck Eiad-ua (My University, 2017)
Humic substance (HS) is very important for soil agriculture that affects physical and chemical properties and improves soil fertility.Humic substances are complex mixtures of polydispersed materials formed by biochemical and chemical reactions during the decay and transformation of plant and microbial remains.Humic substances were extracted from leonardite of lignite Mae Mho Mine in Lampang province by using base-acid treatment and centrifugation.This research studied the effect of time and temperature in base treatment process and the effect of soils particle size.The humic substance which contain humin, humic acid (HAs) and fulvic acid (FAs) were extracted by base-acid treatment.Firstly, soil sample were stirred in base solution and precipitated by centrifugation.The humin precipitate that the fraction is not soluble in water at any pH value was dried at 90 o C.Then, the soluble(HAs and FAs) were pH adjusted to 2 by using 3M HCl and stirred in room temperature The humic fraction precipitate were separated by centrifugation and was dried at 90 o C. The soluble was pH adjusted to 4-5 and settled for 24 hr.The fulvic acid precipitate was dried at 90 o C. Humic substances were studied for element analysis and chemical structure by FT-IR and CHNO.The yields of humic acid were increased at the increase of soils particle size and base reaction time.
Keywords: Metal Extraction and Bioleaching